2020
DOI: 10.1001/jamanetworkopen.2020.3316
|View full text |Cite
|
Sign up to set email alerts
|

State Policies on Access to Vaccination Services for Low-Income Adults

Abstract: IMPORTANCE State vaccination benefits coverage and access for adult Medicaid beneficiaries vary substantially. Multiple studies have documented lower vaccination uptake in publicly insured adults compared with privately insured adults. OBJECTIVE To evaluate adult Medicaid beneficiaries' access to adult immunization services through review of vaccination benefits coverage in Medicaid programs across the 50 states and the District of Columbia. DESIGN, SETTING, AND PARTICIPANTS A public domain document review wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“… 45 Medicaid coverage is also variable. 46 , 47 Our study suggests addressing these voids in coverage will be important to improving national RZV vaccination rates.…”
Section: Discussionmentioning
confidence: 85%
“… 45 Medicaid coverage is also variable. 46 , 47 Our study suggests addressing these voids in coverage will be important to improving national RZV vaccination rates.…”
Section: Discussionmentioning
confidence: 85%
“…For covered vaccines, provider reimbursement often does not fully account for costs. 19 A study of 13 United States medical practices similarly showed Medicaid payments were often insufficient. 20 Reducing financial barriers to providers is part of the United States Department of Health and Human Services's strategy to increase hepatitis vaccination coverage and prevent new infections.…”
Section: Discussionmentioning
confidence: 99%
“…At least eight state programs do not provide separate reimbursement for vaccine administration, and no state provides separate reimbursement for vaccine counseling if a patient refuses vaccination. 26 , 27 Moreover, Medicaid reimbursement payments for adult vaccine administration have been found to be substantially lower than payments from Medicare and private payers. 28 HCP concerns over reimbursement may therefore be a significant barrier to the vaccination of low-income individuals.…”
Section: Discussionmentioning
confidence: 99%